Outstanding performances during elite-standard short and middle-distance finals and the hyperandrogenism regulation—A detailed analysis of Caster Semenya`s results - Ospina-Betancurt, J.; Zakynthinaki, M. S. (Journal of Sports Sciences, 2020)
Recently, there has been much controversy over the International Association of Athletics Federation (IAAF) regulations regarding eligibility to compete and natural testosterone levels in female athletes. Much interest lies in the analysis of Caster Semenya's extraordinary performance. The objective of this work were, a) Complete an analysis of Caster Semenya's results during the 800m finals and b) search for existing similar performances by other female athletes. We analysed the results of the finals of all IAAF World Championships and Olympic Games from 1984-2016, including the 800m results of the Diamond Leagues 2016-2018. Exponential curves were fit to the data to characterise and predict performance for each event. Caster Semenya's finishing times before her ineligibility to compete and after the suspension of the IAAF hyperandrogenism regulation were found to be 1.24% and 1.49%, respectively, faster than the characteristic performance of the elite-standard in the women`s 800m final. Other female athletes, with finishing times faster than the ones predicted by the characteristic curves were also discovered. The percentage difference in performance between Caster Semenya and the other participants did not reach 3% in the 800m event. No conclusions can be drawn regarding extraordinary results ever performed during the 100m, 200m or 400m finals.